Atorvastatin Treatment for Carotid Intima-Media Thickness in Chinese Patients With Type 2 Diabetes: A Meta-Analysis. Issue 44 (November 2015) - Fang, Na; Han, Wei; Gong, Dandan; Zou Chen; Fan, Yu
Abstract : Abstract: Impact of atorvastatin on carotid intima-media thickness (CIMT) in patients with type 2 diabetes is still debating. The aim of our study is to investigate atorvastatin as adjuvant treatment on CIMT in Chinese patients with type 2 diabetes by conducting a meta-analysis based on the randomized controlled trials (RCTs). A systematic search of electronic database of the Pubmed, EMBASE, Cochrane Library, VIP database, China National Knowledge Infrastructure, and Wangfang up to January 2015 was conducted. Randomized controlled trials (RCTs) comparing atorvastatin adjuvant treatment to the hypoglycemic therapies or high-dose atorvastatin versus low-dose atorvastatin therapies for patients with type 2 diabetes were selected. A total of 14 RCTs involving 1345 patients were included. Adjuvant treatment with atorvastatin was associated with a significant reduction in CIMT (weighted mean difference [WMD] = −0.17 mm; 95% confidence interval [CI] −0.22 to −0.12). Compared with the low-dose atorvastatin, high-dose atorvastatin treatment was associated with a significant reduction in CIMT (WMD = −0.17 mm; 95% CI: −0.32 to −0.02). Adjuvant treatment with atorvastatin reduced serum total cholesterol, triglyceride, low-density lipoproteins, and high sensitivity C-reactive protein levels. However, atorvastatin had no significant impact on blood glucose levels. This meta-analysis demonstrated that treatment with atorvastatin significantly reduced CIMT in Chinese patients with type 2 diabetes. Moreover, high-dose atorvastatin appeared to have additional benefits in reducing CIMT than the low-dose atorvastatin.